CORPORATE SOCIAL RESPONSIBILITY DAN KINERJA PERBANKAN DI INDONESIA - Bestari Dwi Handayani (University of Merdeka Malang, 2012)
The focus of this research was on corporate banking sector. Based on the background, the problem in this studywas the influence of CSR parameters (community, employment, product and consumer, and environment)toward return on assets as the proxy of banking performance. This study used multiple regression analysis todetermine the influence of CSR parameters (community, employment, product and consumer, and environment)toward the Return on Assets in the banking sector companies listed in Indonesia Stock Exchange. Theresults showed CSR community and CSR employment had positive and significant impact toward ROA,while CSR environment had negative impact and it was not significant to ROA. This study could not explainthe influence of CSR and Consumer Product toward ROA.